Tanshinone IIA alleviates cardiac hypertrophy through m6A modification of galectin-3. Issue 2 (1st February 2022) - Zhang, Meiqi; Chen, Yun; Chen, Huan; Shen, Ye; Pang, Lingxiao; Wu, Weihua; Yu, Zhenfei
ABSTRACT: Cardiac hypertrophy results from the adaptive response of the myocardium to pressure overload on the heart. Tanshinone IIA (Tan IIA) is the major active compound extracted from Salvia miltiorrhiza Bunge, which possesses various pharmacological benefits. In the present study, the effect and mechanism of action of Tan IIA on cardiac hypertrophy were studied. Ang II–induced and transverse aortic constriction (TAC)-induced cardiomyocyte hypertrophy models were used to evaluate the effect of Tan IIA. An adenoviral vector system was utilized to overexpress galectin-3. The results revealed that Tan IIA significantly inhibited Ang II–induced hypertrophy in vitro and TAC-induced cardiac hypertrophy in vivo . Furthermore, Tan IIA notably inhibited the expression of galectin-3. Rescue experiments indicated that galectin-3 overexpression reversed the effects of Tan IIA, which further validated the interaction between Tan IIA and galectin-3. Additionally, Tan IIA suppressed alkB homolog 5, RNA demethylase (ALKBH5)-mediated N6-methyladenosine (m6A) modification of galectin-3. In summary, the results of the present study indicated that Tan IIA attenuates cardiac hypertrophy by targeting galectin-3, suggesting that galectin-3 plays a critical role in cardiac hypertrophy and represents a new therapeutic target.